2021
DOI: 10.1073/pnas.2014920118
|View full text |Cite
|
Sign up to set email alerts
|

Molecular reprogramming and phenotype switching in Staphylococcus aureus lead to high antibiotic persistence and affect therapy success

Abstract: Staphylococcus aureus causes invasive infections and easily acquires antibiotic resistance. Even antibiotic-susceptible S. aureus can survive antibiotic therapy and persist, requiring prolonged treatment and surgical interventions. These so-called persisters display an arrested-growth phenotype, tolerate high antibiotic concentrations, and are associated with chronic and recurrent infections. To characterize these persisters, we assessed S. aureus recovered directly from a patient suffering from a persistent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 54 publications
(60 reference statements)
4
71
0
Order By: Relevance
“…In agreement with this, antibiotic efficacy positively correlates with metabolic activity in the cell [44,45]. Interestingly, it has also been shown that in the infection environment, interactions of S. aureus with other pathogens or with the host immune system can both impact its metabolic activity and induce a decrease in ATP level and an increase in antibiotic tolerance [46][47][48].…”
Section: Plos Biologysupporting
confidence: 56%
“…In agreement with this, antibiotic efficacy positively correlates with metabolic activity in the cell [44,45]. Interestingly, it has also been shown that in the infection environment, interactions of S. aureus with other pathogens or with the host immune system can both impact its metabolic activity and induce a decrease in ATP level and an increase in antibiotic tolerance [46][47][48].…”
Section: Plos Biologysupporting
confidence: 56%
“…We recently found elevated levels of proteins involved in protein, nucleotide and aminoacid biosynthesis in a persister-enriched population of a clinical isolate of S. aureus that was isolated from a difficult-to-treat infection, 38 . Higher levels of PknB might lead to increased phosphorylation levels that in turn can reduce translation, alter cell wall synthesis and can lead to decreased intracellular ATP levels.…”
Section: Discussionmentioning
confidence: 99%
“…4A). Here, we used the less cytotoxic Cowan I to induce abscess formation and pus production in the mice as described previously 13,38 . Five days post-infection, mice were sacrificed, abscess size measured, and the pus harvested for further analysis.…”
Section: Stp Deletion Leads To Increased Bacterial Lag-phase and Antibiotic Persistence In Micementioning
confidence: 99%
“…MAU : Pleasecheckwhethertheeditstothesentence acrophages induce antibiotic tolerance of internalized S. aureus through reactive oxygen species (ROS) that cause collapse of the tricarboxylic acid (TAU : PleasenotethatTCAhasbeendefinedastricarboxylicacidinthesentenceMacropha CA) cycle an entrance to a low ATP state [6]. Additionally, activation of the stringent response has also been shown to contribute to S. aureus intracellular tolerance [7], while neutrophil interaction as well as acid stress have also been shown to induce antibiotic tolerance in S. aureus abscess patient isolates [21]. In Salmonella Typhimurium, antibiotic-tolerant persister subpopulations are induced intracellularly through acid stress, nutritional deprivation, and the activation of toxin-antitoxin modules [9].…”
Section: Is the Immune Response Responsible For Poor Antibiotic Efficacy?mentioning
confidence: 99%